Corporate social reporting in Malaysia: A political theory perspective / Azlan Amran and S. Susela Devi - Amran, Azlan; S., Susela Devi (UPENA, 2007)
This study explores the influence of the government in the development Corporate Social Reporting (CSR) in the Malaysian context. It explains CSR disclosure in annual reports of public listed companies using a political economy theory perspective. An examination of 201 annual reports of Malaysian companies reveals the influence of the government in CSR disclosure. Generally, the reporting practice of the companies sampled support political economic theory since both variables used in this study, government shareholding and dependence on the government, were found to be significant. The findings indicate that the government has a potential to play a significant role in spearheading CSR practice more intensively, as companies that are dependent on the government or with significant government shareholding are institutionalized by the government's aspiration and vision with respect to social and environmental issues. The findings reveal that employee and environmental themes are the most commonly disclosed information by those companies.